PERGESERAN BAHASA SEBAGAI DAMPAK SIKAP BAHASA - Pratiwi, Dwiyani (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
impacts on the development of the languages used by the community concerned.One of the impacts is language shift. Factors that are conducive to language shiftare varied. One of these factors is language attitude. This article discusses a furtherimpact that language shift itself can in turn cause, i.e., language death, its process,and the efforts made by individuals, social groups, and the government in authorityto maintain the existence of a language, which implies language maintenance.Keywords: language shift, language maintenance